2021
DOI: 10.2147/idr.s275852
|View full text |Cite
|
Sign up to set email alerts
|

Detection of gyrA and parC Mutations and Prevalence of Plasmid-Mediated Quinolone Resistance Genes in Klebsiella pneumoniae

Abstract: Background and Aim Recently, the extensive use of quinolones led to increased resistance to these antimicrobial agents, with different rates according to the organism and the geographical region. The aim of this study was to detect the resistance rate of Klebsiella pneumoniae Iraqi isolates toward quinolone antimicrobial agents, to determine genetic mutations in gyrA and parC , to screen for efflux-pump activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 64 publications
8
41
3
Order By: Relevance
“…Among 100 isolates four (3.8%) isolates which were showing resistance to Ciprofloxacin by MIC method were sent for molecular detection for Gyr A and Par C gene all 4 isolates were positive for both the genes. This study correlates Kareem et al, (16) the Gyr A gene was detected by PCR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among 100 isolates four (3.8%) isolates which were showing resistance to Ciprofloxacin by MIC method were sent for molecular detection for Gyr A and Par C gene all 4 isolates were positive for both the genes. This study correlates Kareem et al, (16) the Gyr A gene was detected by PCR.…”
Section: Discussionsupporting
confidence: 91%
“…The resistance to Cotrimoxazole was 64% and resistance to Ciprofloxacin 60%. In the study of Kareem et al, (16) The antimicrobial agents tested included meropenem, imipenem, tigecycline, Ciprofloxacin, aztreonam, amikacin, levofloxacin, cefoperazone-sulbactam, cefotaxime, cefepime, and trimethoprim/sulfamethoxazole. The highest susceptibility were found to be towards the Cefoperazone-sulbactam 48% and the highest rate of resistance were found to be towards Amikiacin 82% which is least similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…The crisis of MDR bacterial infection was more frequently occurring in developing countries. K. pneumoniae , as the second most common nosocomial gram-negative bacterium, leads to significantly high all-cause mortality in worldwide [ 10 , 12 , 14 , 25 ]. Carbapenem, amikacin and tigecycline used to be effective and latest antibiotics for MDR- K. pneumoniae treatments, but recent researches revealed that drug-resistance rates of these three antibiotics were significantly increasing which may be associated with overuse during treatments [ 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breakpoints of minimum inhibitory concentration (susceptible, resistant) for each antibiotics were according to the Clinical Laboratory Standard Institute guidelines: amoxicillin-clavulanate (≤ 8/4, ≥ 32/16 μg/ml), amikacin (≤ 16, ≥ 32 μg/ml), aztreonam (≤ 4, ≥ 16 μg/ml), ciprofloxacin (≤ 0.25, ≥ 1 μg/ml), gentamicin (≤ 4, ≥ 16 μg/ml), imipenem (≤ 2, ≥ 8 μg/ml), meropenem (≤ 2, ≥ 8 μg/ml), levofloxacin (≤ 0.5, ≥ 2 μg/ml), sulfamethoxazole (≤ 2/38, ≥ 4/76 μg/ml), piperacillin-tazobactam (≤ 16/4, ≥ 128/4 μg/ml), ceftriaxone (≤ 8, ≥ 64 μg/ml) and tigecycline (≤ 2, ≥ 8 μg/ml). MDR- K. pneumoniae was defined as the strain non-susceptible to at least one agent in three or more antimicrobial categories [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation